2008
DOI: 10.1056/nejmoa0708789
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm Control versus Rate Control for Atrial Fibrillation and Heart Failure

Abstract: In patients with atrial fibrillation and congestive heart failure, a routine strategy of rhythm control does not reduce the rate of death from cardiovascular causes, as compared with a rate-control strategy. (ClinicalTrials.gov number, NCT00597077.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
836
3
59

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,413 publications
(930 citation statements)
references
References 39 publications
12
836
3
59
Order By: Relevance
“…52,53,54,55 These studies have demonstrated no difference in these endpoints. When interpreting the results of these studies, it is important to keep in mind the population of patients who were enrolled, the approach used for rhythm control, and the duration of follow-up.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 92%
“…52,53,54,55 These studies have demonstrated no difference in these endpoints. When interpreting the results of these studies, it is important to keep in mind the population of patients who were enrolled, the approach used for rhythm control, and the duration of follow-up.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 92%
“…Leki antyarytmiczne powodują w przybliżeniu podwojenie częstości utrzymywania rytmu zatokowego w porównaniu z placebo [580][581][582][583][584]. Gdy leki antyarytmiczne zawiodą, często skuteczna jest ablacja przezcewnikowa lub leczenie skojarzone [226,[585][586][587].…”
Section: Leczenie W Celu Kontroli Rytmu Serca U Pacjentów Z Migotanieunclassified
“…Gdy leki antyarytmiczne zawiodą, często skuteczna jest ablacja przezcewnikowa lub leczenie skojarzone [226,[585][586][587]. Choć wielu klinicystów sądzi, że utrzymywanie rytmu zatokowego może poprawiać wyniki leczenia u pacjentów z AF [588], to we wszystkich próbach klinicznych, w których porównano kontrolę rytmu serca i kontrolę częstości rytmu komór z samą kontrolą częstości rytmu komór (w połą-czeniu z odpowiednim leczeniem przeciwzakrzepowym), uzyskano neutralne wyniki leczenia [41,578,579,582,[589][590][591][592][593]. Kwestia, czy współczesne postępowanie w celu kontroli rytmu serca, obejmujące ablację przezcewnikową, leczenie skojarzone oraz wczesne leczenie, prowadzi do Podczas stosowania strategii kontroli częstości rytmu komór jako początkowy cel leczenia należy rozważyć częstość rytmu komór w spoczynku < 110 uderzeń na minutę (tj.…”
Section: Leczenie W Celu Kontroli Rytmu Serca U Pacjentów Z Migotanieunclassified
See 1 more Smart Citation
“…However, the side effects, toxicities, and incomplete effectiveness of antiarrhythmic drugs (AADs) may offset their potential benefits 4. Indeed, studies of AADs as a rhythm control strategy—namely amiodarone—have not identified benefits of maintaining sinus rhythm,5, 6 a finding that appears to extend to patients with HF irrespective of ejection fraction (EF) 7, 8. Thus, alternative approaches to rhythm control are being explored.…”
Section: Introductionmentioning
confidence: 99%